Pengenalan Cyber Security Bagi Siswa Sekolah Menengah Atas - Tandirerung, Veronika Asri; Riana T. Mangesa; Syahrul (Jurusan Teknik Informatika dan Komputer, 2023)
Efforts to increase awareness, knowledge and skills in internet safety need attention, especially for children and adolescents. They considered that the Internet had become an inseparable part of the daily life of children and adolescents in Indonesia. It can be achieved through outreach, literacy education and training. Understanding the use and safety of digital media is especially important from the perspective of children and adolescents. They must understand how to use digital technology, online communication and risky or unsafe behaviour. In addition, special attention is needed to provide information for children and adolescents about the risks of harm that may arise from a direct encounter with someone they have just met from cyberspace. Parents and teachers must be aware of and involved in digital safety programs for children and youth. Children and youth must continue to be motivated to view and use the internet as a valuable source of information and to make the most of digital technology to assist in education, increase knowledge, expand opportunities and empower them to achieve a better quality of life. This PKM implementation method is an open-design model method. The open design model consists of three stages: planning, workshop implementation and evaluation. After carrying out the activity, it is expected that students can use social media accounts wisely and know how to protect themselves and others.